A Single Molecular Stoichiometric P‐Source for Phase‐Selective Synthesis of Crystalline and Amorphous Iron Phosphide Nanocatalysts. Issue 8 (19th May 2020) - D'Accriscio, Florian; Schrader, Erik; Sassoye, Capucine; Selmane, Mohamed; André, Rémi F.; Lamaison, Sarah; Wakerley, David; Fontecave, Marc; Mougel, Victor; Le Corre, Grégoire; Grützmacher, Hansjörg; Sanchez, Clément; et al.
Abstract: The formation of iron phosphide nanoparticles (Fe x P NPs) is a well‐studied process. It usually uses air‐sensitive phosphorus precursors such as n ‐trioctylphosphine or white phosphorus. In this study, we report the synthesis and characterization of a remarkably stable tetrakis(acyl)cyclotetraphosphane, P4 (MesCO)4 . We demonstrate that this compound can be used as a stoichiometric source of P(0) species in order to synthesize FeP and Fe2 P nanoparticles at only 250 °C. This tunable process provides a route to monodisperse nanoparticles with different compositions and crystallinities. We combine X‐Ray photoelectron spectroscopy (XPS) and atomic pair distribution function (PDF) in order to study the local order and bonding in the amorphous and crystalline materials. We show that crystalline FeP forms via an intermediate amorphous phase (obtained at a lower temperature) that presents local order similar to that of the crystalline sample. From the results of this work, a better understanding of the mechanism of the formation of amorphous and crystalline Fe x P NPs is provided which relies on the use of a stoichiometric and single P‐source. We then explore the electrocatalytic properties of Fe x P nanoparticles for the hydrogen evolution reaction (HER) in acidic and neutral electrolytes. In both electrolytes, amorphous FeP is a more efficient catalyst than crystalline FeP, itself more efficient than crystalline Fe2 P. Our study paves the way for a more systematic investigation of amorphous metal phosphide phases in electrocatalysis. It also shows the beneficial properties of PDF on the characterization of such nanomaterials, which is highly challenging. Abstract : Phase‐controlled FeP and Fe2 P nanoparticles are prepared using a cyclophosphane at 250 °C. At 180 °C, amorphous compounds are formed yet they present the local structure of the crystalline phases. Amorphous FeP is more active in HER than the corresponding crystalline nanocatalysts.